A Sumerian Inscription of the Fuente Magna, La Paz, Bolivia - Marini, Alberto
General Dr.; John Kennedy University, Buenos Aires; fig. 1: Cuneiform text inscribed on the Magna Fountain, now in the Museo Murillo, Ciudad de la Paz. - p. 13 bottom: Photo of a "Cuneiform tablet found in the ownership of the Nez Perce Indians of Montana